Rural poverty reduction through centrally sponsored schemes - Saxena, N C (Indian journal of medical research (New Delhi, India : 1994), 2007)
This paper discusses the evolving profile of poverty in India and reviews the national performance of selected anti-poverty programmes between 1997-1998 and 2005. For each programme, it outlines the budgetary allocation principle used for the States and districts and analyzes budgetary performance over the period. The main objective is to explore the extent to which the anti-poverty programmes are reaching their target groups effectively. Finally, it identifies the specific factors responsible for under-performance and provides a set of recommendations for policy makers and programme implementers which could help improve the outcomes of the schemes.